Effect of monetary policy rate on market interest rates in Nigeria: A threshold and NARDL approach - Oluwafemi E. Awopegba; Joseph O. Afolabi; Lydia T. Adeoye; Godwin O. Akpokodje (CBN Journal of Applied Statistics, 2022)
This study examines the effect of monetary policy rate (MPR) on market interest rates in Nigeria. For parsimony, we develop two indexes called the short-term in- terest rate (SINT) and Lending interest rate (LINT) to represent deposit and lending rates respectively. The nonlinear autoregressive distributed lag (NARDL) and thres- hold regression models are adopted. The study uses monthly data from 2002:M1 to 2019:M12. The results of the threshold regression model indicate that the degree of the effect of MPR on SINT and LINT above the estimated threshold of 11 and 13 percent respectively is greater and significant than if MPR were to be below the threshold. Moreover, estimates from the nonlinear ARDL model show that increas- ing MPR induces a positive effect on short-term and lending interest rates, while a negative effect holds if MPR is decreased. For LINT, the magnitude of the negative effect is little, while for SINT, the effect is statistically insignificant. This depicts the downward stickiness of prices, which supports the argument that the inefficitveness of MPR only holds when it is adjusted downward. We recommend that the monetary authority should focus on reforming the banking system in ways that remove down- ward rigidities in the effect of MPR on interest rates in order to engender greater efficiency of monetary policy.
Keywords: C22; C24; E43; E52; E58; 330; Interest rate; monetary policy rate; nonlinear threshold regression